New competences of the Roman Rota concerning the procedures for the disolution of non consummated marriages and the cases for declaring the nullity of sacred ordination: the Motu Proprio «Quaerit semper», of Benedicto XVI - Peña García, Carmen (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
The Apostolic Letter «Motu Proprio data» Quaerit semper (August 30, 2011), from the Pope Benedict XVI, has amended some articles of the Apostolic Constitution Pastor Bonus. This Apostolic Letter has transferred the competence for handling the procedures involving the pontifical dissolution of non-consummated marriages and also the cases for declaring the nullity of sacred ordination from the Congregation for Divine Worship and the Discipline of the Sacraments to a new Office established within the Roman Rota. In this article, the author analyses the contents of this Apostolic Letter and makes some reflections on its application and on the opportunity to introduce some other changes in the regulation of the procedures involving non-consummated marriages, in order to allow the intervention of lawyers in these processes.